2010
DOI: 10.1371/journal.pgen.1001074
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated Mutations That Alter the RNA Structural Ensemble

Abstract: Genome-wide association studies (GWAS) often identify disease-associated mutations in intergenic and non-coding regions of the genome. Given the high percentage of the human genome that is transcribed, we postulate that for some observed associations the disease phenotype is caused by a structural rearrangement in a regulatory region of the RNA transcript. To identify such mutations, we have performed a genome-wide analysis of all known disease-associated Single Nucleotide Polymorphisms (SNPs) from the Human G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
334
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(342 citation statements)
references
References 75 publications
7
334
0
1
Order By: Relevance
“…Because the precise functions of the majority of lincRNA sequences remain unknown, it is difficult to identify the molecular cause of disease-associated SNPs located in lincRNAs. Previous studies have shown that functional noncoding regions in the human genome had conserved RNA secondary structures, 44 and certain human diseases could be caused by variants inducing structural changes, 28 suggesting RNA structural change as a potential molecular cause of the disease. Our results found that some known disease-associated SNPs located in lincRNAs had significant effects on predicted RNA secondary structures, which might have causal effects on disease risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the precise functions of the majority of lincRNA sequences remain unknown, it is difficult to identify the molecular cause of disease-associated SNPs located in lincRNAs. Previous studies have shown that functional noncoding regions in the human genome had conserved RNA secondary structures, 44 and certain human diseases could be caused by variants inducing structural changes, 28 suggesting RNA structural change as a potential molecular cause of the disease. Our results found that some known disease-associated SNPs located in lincRNAs had significant effects on predicted RNA secondary structures, which might have causal effects on disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we used a significance calculation to search for the large structural changes caused by SNPs. 28 We computed a P-value for each lincRNA polymorphism, which was based on the total number of SNPs in a lincRNA divided by the rank of the SNP's MFE change in this lincRNA.…”
Section: Rna Secondary Structure Prediction and Significance Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, investigators focused on genetic variants in regulatory regions as the cause of abnormities in gene expression during carcinogenesis. Next, more diseases have been correlated with changes in those regions (Conne et al, 2000;Pickering & Willis, 2005;Chen et al, 2006;Sethupathy & Collins, 2008;Halvorsen et al, 2010).…”
Section: Rna Profile Identification)mentioning
confidence: 99%
“…Lam et al demonstrated that a 50% reduction in eRNA expression reduces the expression of target genes by a similar magnitude so the disruption of eRNA production may represent a novel mechanism by which risk SNPs act to alter local gene expression [232]. It is also interesting to note that SNP1 is contained within the sequence of the (+) strand eRNA raising the question whether it may represent a riboSNitch inducing a conformational change in RNA structure and hence alter the function of the eRNA [312].…”
Section: )mentioning
confidence: 99%